Perancangan Grafis Lingkungan di Area Alas Outbound Prambon Dusun Ngingas Desa Wisata Simpang - Adi Setyawan; Sri Wulandari (Institut Nalanda, 2023)
Ngingas Hamlet is an area located in Simpang Village, Prambon District, Sidoarjo Regency, East Java. This hamlet has a tourist attraction called Alas Outbound or better known as Alas Prambon. However, in Ngingas Hamlet it is felt that it has good potential by adding a village mural and there is still a lack of dena in Alas Outbound tourism and there is still no RT / RW sign. The purpose of this design is to create an environmental graphic design that is applied according to the needs of Ngingas Hamlet.This environmental graphic aims to find out the layout, location plan and identity of the head of the RT / RW in Ngingas Hamlet, as well as beautify Ngigas Hamlet by making a village mural so that visitors get a happy atmosphere when visiting Alas Outbound.Data collection methods used in this design include observation, literature study, documentation and interviews. Ngingas Hamlet is an area located in Simpang Village, Prambon District, Sidoarjo Regency, East Java. This hamlet has a tourist attraction called Alas Outbound or better known as Alas Prambon. However, in Ngingas Hamlet it is felt that it has good potential by adding a village mural and there is still a lack of dena in Alas Outbound tourism and there is still no RT / RW sign. The purpose of this design is to create an environmental graphic design that is applied according to the needs of Ngingas Hamlet.This environmental graphic aims to find out the layout, location plan and identity of the head of the RT / RW in Ngingas Hamlet, as well as beautify Ngigas Hamlet by making a village mural so that visitors get a happy atmosphere when visiting Alas Outbound.Data collection methods used in this design include observation, literature study, documentation and interviews